Visual Discomfort and Depth-of-Field. (May 2013) - O'Hare, Louise; Zhang, Tingting; Nefs, Harold T.; Hibbard, Paul B.
Visual discomfort has been reported for certain visual stimuli and under particular viewing conditions, such as stereoscopic viewing. In stereoscopic viewing, visual discomfort can be caused by a conflict between accommodation and convergence cues that may specify different distances in depth. Earlier research has shown that depth-of-field, which is the distance range in depth in the scene that is perceived to be sharp, influences both the perception of egocentric distance to the focal plane, and the distance range in depth between objects in the scene. Because depth-of-field may also be in conflict with convergence and the accommodative state of the eyes, we raised the question of whether depth-of-field affects discomfort when viewing stereoscopic photographs. The first experiment assessed whether discomfort increases when depth-of-field is in conflict with coherent accommodation–convergence cues to distance in depth. The second experiment assessed whether depth-of-field influences discomfort from a pre-existing accommodation–convergence conflict. Results showed no effect of depth-of-field on visual discomfort. These results suggest therefore that depth-of-field can be used as a cue to depth without inducing discomfort in the viewer, even when cue conflicts are large.